PENGGUNAAN APLIKASI PERPAJAKAN BERBASIS ELEKTRONIK DI BADAN PENDAPATAN DAERAH KABUPATEN BLITAR MENUJU ERA DIGITAL - Suryani Suryani; Edy Swasono (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This study aims to examine the function and usefulness of the results of the Use of Electronic-Based Taxation Applications in the Regional Revenue Agency of Blitar District Towards the Digital Era, which hopes taxpayers and tax officers can easily carry out tax transactions. The results of this study are expected to provide benefits, among others: (1) For Bapenda of Blitar District, this research can be used as an evaluation material regarding the level of understanding of taxpayers and tax officials in using electronic-based taxation applications and can be followed up with socialization on how to use tax-based applications electronic properly and thus minimizes the level of errors that occur due to human error. (2) For researchers, provide researchers with knowledge about the problems faced by taxpayers and tax officials in using electronic-based taxation applications and their causes, as well as honing the ability of researchers to find solutions to that understanding. (3) For taxpayers, it is hoped that this research can solve the problems encountered when using electronic-based taxation applications. (4) For tax officers, it is hoped that this research can solve the problems encountered when working using electronic-based taxation applications This qualitative approach uses a descriptive approach, namely: a study conducted on a causal-effect (cause-and-effect) event or phenomenon that has occurred, the cause of which is not due to the treatment / intervention of the researcher. In this method the research subject of Siridoaja Tax Application in Blitar Regency Regional Revenue Agency, Taxpayers and Tax Officers This research data uses secondary data taken from Blitar District Bapenda data. This research design using field studies is a research design that combines literature search (Literature Study), surveys based on experience or relationships between these variables in a particular problem situation. From this research it was found that: (1) This system was built to provide a solution and convenience for taxpayers to get fast and complete information about PBB-P2 and to find out the truth of the amount of tax they have. (2) Factors that constrain the use of electronic-based applications are unequal internet access, operator capacity in using applications, and the ability of taxpayers to operate Siridoaja applications (3) The advantages of electronic-based Siridoaja applications in their use are accurate and accountable so that if there are errors entries / data can be viewed immediately by the operator or taxpayer. (4) Evaluation of the use of the Siridoaja application that this application can be utilized to the maximum both by the Tax Officer and the general public who can already enjoy online tax service facilities